On the Languages of Markets (The Distinguishedl Lecture) (The Pakistan Development Review, 1991)
In this essay, I look at differing conceptions of the market, ranging from the concrete where it is regarded simply as a place, to the abstract where it is looked on both as power and as a principle, and where its attendant vocabulary can be used to give meaning and distinction to the relation between God and man.1 As such, I want to look at market, not as a keyword in the terminology of Raymond Williams,2 but as a concept3 with widely differing meaning across cultures, and more specifically, across time within the same culture. Even though this opens up a vast subject, what makes the project manageable, and in line within the limits of my _own competence, is the motivation which leads me to undertake it. My primary motivation is to show that the language of economic theory in the last half century has undergone a shift in orientation and emphasis, and this shift has had, as an important corollary, a corresponding shift in our normative and evaluative stance towards markets and exchange. I document these shifts and set them in other contexts to show that they reflect an age-old tension between differing conceptions of man and society, and of individual self-interest and the larger public interest. I examine how these conceptions are seen with reference to each other, and how the meaning given to the term market leads them to conflict or coincide.